2017
DOI: 10.1371/journal.pone.0171723
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of opioid efficacy in patients with chronic pain: A prospective multicenter observational cohort study

Abstract: Opioids are increasingly used for treatment of chronic pain. However, they are only effective in a subset of patients and have multiple side effects. Thus, studies using biomarkers for response are highly warranted. The current study prospectively examined 63 opioid-naïve patients initiating opioid use for diverse types of chronic pain at five European centers. Quantitative sensory testing, electroencephalography (EEG) recordings, and assessment of pain catastrophizing were performed prior to treatment. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…Yet, the study by Grosen et al. (Grosen et al., ) identified pain catastrophizing as a significant predictor for opioid efficacy. It must be noted, however, that their study population included patients with various pain syndromes, including head, neck and other musculoskeletal as well as neuropathic pain patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the study by Grosen et al. (Grosen et al., ) identified pain catastrophizing as a significant predictor for opioid efficacy. It must be noted, however, that their study population included patients with various pain syndromes, including head, neck and other musculoskeletal as well as neuropathic pain patients.…”
Section: Discussionmentioning
confidence: 99%
“…These studies identified a selection of QST to predict treatment response, but the sample sizes were generally small, and the results are not consistent across studies. The most recent evidence (Grosen et al., ) showed that opioid efficacy was predicted by low levels of pain catastrophizing, low pain intensity during cold pressor stimulus of the hand and certain EEG patterns. The patient population in this study was very heterogeneous in terms of pain syndrome and pain location.…”
Section: Introductionmentioning
confidence: 99%
“…Three arguments are usually set forth to uphold this prospect in the field of pain neuroimaging ( Kupers and Kehlet, 2006 ; Borsook et al , 2007 , 2010 ; de Vries et al , 2013 ; Lee and Tracey, 2013 ; Morton et al , 2016 ; Grosen et al , 2017 ; Tracey, 2017 ). First, it is often claimed that functional neuroimaging could be used to derive brain biomarkers that measure pain ‘objectively’.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, baseline QST responses have been associated with the efficacy of lidocaine, lamotrigine, pregabalin, oxycodone, oxcarbazepine, and placebo analgesia. 50 In a multicenter observational cohort study, Grosen et al 76 found that opioid response was predicted by cold pain intensity, pain catastrophizing, and beta EEG activity induced by laboratory cold pain in a small sample of mixed-type chronic pain patients. Pretreatment pain inhibition, often measured through conditioned pain modulation (counterirritation believed to reflect descending pain control 156 ), has been associated with postoperative pain outcomes, 13,183 the benefits of exercise, 103 morphine consumption after chest wall surgery, 77 duloxetine benefit in painful diabetic neuropathy patients, 185 and NSAID efficacy.…”
Section: Mechanism-based Approach To Analgesic Trialsmentioning
confidence: 99%